Organic electrochemical transistors based on PEDOT with different anionic polyelectrolyte dopants. Issue 2 (20th October 2015) - Inal, Sahika; Rivnay, Jonathan; Hofmann, Anna I.; Uguz, Ilke; Mumtaz, Muhammad; Katsigiannopoulos, Dimitrios; Brochon, Cyril; Cloutet, Eric; Hadziioannou, Georges; Malliaras, George G.
ABSTRACT: Recent applications of organic electrochemical transistors (OECTs) in bioelectronics motivate the search for new materials with mixed electronic and ionic conductivity. We investigate the characteristics of a series of poly(3, 4‐ethylenedioxythiophene) (PEDOT)‐based materials with a new class of anionic polyelectrolytes used as dopants and stabilizers, replacing the traditionally used poly(styrene sulfonate) (PSS). We show that the backbone of the polyanion plays a major role in determining device performance, while its molecular weight and the counter ion used during PEDOT synthesis play a less important role. We find that transconductance increases with the degree of swelling of the film, consistent with enhanced ion transport. Finally, we identify a polymer that offers performance close to the state‐of‐the‐art. This work highlights the importance of the polyanion phase as a means to control OECT performance. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2016, 54, 147–151 Abstract : Recent applications of organic electrochemical transistors (OECTs) in bioelectronics motivate the search for new materials with mixed electronic and ionic conductivity. In this work, the characteristics of a series of poly(3, 4‐ethylenedioxythiophene) (PEDOT)‐based materials with a new class of polyanionic dopants, replacing the traditionally used poly(styrene sulfonate) (PSS), is investigated. The backbone of the polyanion plays a major role in determining device performance, while its molecular weight and the counter ion used during synthesis are less significant.